Síntese e análise estrutural de novos tetrahaloorganoteluratos(IV) monoaniônicos e hexahaloteluratos(IV) dianiônicos - Fernandes Júnior, Ramão Marceli (2004)
This work presents our contribution about the solid state of new anionic tetrahaloorganyltellurates(IV) and dianionic hexahalotellurates(IV) compounds. We present the synthesis and structural characterization of seven new compounds with a general formula Q[PhTeX4]: (2-Br C5H5N)[PhTeI4] (1), (2-Br C5H5N)[PhTeBr4] (2), (2-Br C5H5N)[PhTeCl4] (3), (C5H6N)[PhTeCl4] (4), (2-Br C5H5N)[CoCl2(NH3)4] [PhTeCl4]2 (5), Cs[PhTeCl4]·CH3OH (6), Cs[PhTeBr4] (7) and two compounds with a general formula Q2[TeX6]: (2-Br C5H5N)2[TeX6], X = Cl (8) and Br (9). The synthesis of 1 to 4 occurred by the reaction of diphenylditelluride (PhTe)2, acid (HX) and the corresponding cation Qn+. The acid furnish the oxidation of diphenylditelluride. The compounds 1 to 4 in the solid state are stable in presence of air and water. The compound (2-Br C5H5N)[CoCl2(NH3)4][PhTeCl4]2 (5) have been obtained after partial exchange of the cation (2-Br C5H5N)+ in 3 for the ion tetramindichlorocobalt(III), [CoCl2(NH3)4]+. The compound Cs[PhTeCl4]·CH3OH (6) was obtained by the reaction between PhTeCl3 and CsCl in methanol. The compound Cs[PhTeBr4] (7) was obtained by the reaction between the compound 2 and CsCl and a excess of HBr in ethanol. The synthesis of (2-Br C5H5N)2[TeX6] occurred by the reaction of tellurium tetrahalide (TeX4) and acid (HX) and 2-bromopyridine, X = Cl (8) and Br (9). The compounds 7 and 8 are stable, but 5, 6 and 9 decompose in presence of water and air. The compounds show general structural characteristic and are very similar because they present a relationship tellurium-halide secondary bonds and X X and Cs X interaction and hydrogen bonds between the halides. The compounds (2-Br C5H5N)[PhTeX4], X = I (1) and Br (2) show a supramolecular structure. (2-Br C5H5N)[PhTeCl4] (3) and (C5H6N)[PhTeCl4] (4) present a dimeric and a trimeric form, respectively. The compound 5 shows different cations, (2-Br C5H5N)+ and [CoCl2(NH3)4]+. The pseudo-dimeric form occurred through hydrogen bonds (Co NH3 Cl) between the ions [CoCl2(NH3)4]+ and [PhTeCl4]-, generating an supramolecular structure. The compound 1 to 5 show multicentered hydrogen bond. The compounds Cs[PhTeCl4]·CH3OH (6) and Cs[PhTeBr4] (7) presents a tridimensional supramolecular arrangements organized basically by interactions between cesium and [PhTeX4]- groups. In 6 a molecule of methanol produce a Cs O Cs bridge by a interaction between the cesium atoms. In 7 the ion cesium presents a coordination derivative from a pentagonal prism. The prisms are connected along the axis a. The compounds (2-Br C5H5N)2[TeX6], X = Cl (8) and Br (9), present a bidimensional supramolecular building. In 8 the arrangement is organized by intermolecular interactions by hydrogen bonds H X tricentered. In 9 the structural arrangement occurred between week Br Br interactions and hydrogen bonds H X tricentered.